Longitudinal Influences of DRD4 Polymorphism and Early Maternal Caregiving on Personality Development and Problem Behavior in Middle Childhood and Adolescence - Zimmermann, Peter; Spangler, Gottfried (Frontiers in Human Neuroscience, 2022)
Most studies examining gene-environment effects on self-regulation focus on outcome at early childhood or adulthood. However, only few studies investigate longitudinal effects during middle childhood and adolescence and compare two aspects of early caregiving. In a longitudinal follow-up with a sample of N=88, we studied the effects of differences in the DRD4 tandem repeat polymorphisms and two aspects of early maternal caregiving quality on children’s personality development using Block’s California Child Q-Set (CCQ) at age six and age twelve and on problem behavior at ages six and seven. Early maternal regulation quality predicted later ego-resiliency and aggressiveness. In addition, significant gene-environment interactions revealed that children with the 7+ DRD4 tandem repeat polymorphism and poor maternal regulation quality in infancy showed lower scores in ego-resiliency and higher scores in ego-undercontrol and CCQ aggressiveness. In contrast, children who had experienced effective maternal regulation in infancy showed a comparable level as the DRD4 -7 group independent of the levels of maternal regulatory behavior. Similarly, longitudinal caregiving x DRD4 interactions were found for behavior problems in middle childhood, especially for oppositional-aggression, inattentive-hyperactivity, and social competence. Early caregiving effects were only found for maternal regulation quality, but not for maternal responsiveness. Effective early maternal regulation in infancy can moderate the negative effect of DRD4 7+ on children’s self-regulation in middle childhood and adolescence. However, maternal responsiveness has no comparable effects. It is relevant to consider several dimensions of early caregiving for gene-environment studies.